2006
DOI: 10.37236/1115
|View full text |Cite
|
Sign up to set email alerts
|

Matchings Avoiding Partial Patterns and Lattice Paths

Abstract: In this paper, we consider matchings avoiding partial patterns $1123$ and $1132$. We give a bijection between $1123$-avoiding matchings with $n$ edges and nonnegative lattice paths from $(0,2)$ to $(2n,0)$. As a consequence, the refined enumeration of $1123$-avoiding matchings can be reduced to the enumeration of certain lattice paths. Another result of this paper is a bijection between $1132$-avoiding matchings with $n$ edges and lattice paths from $(0,0)$ to $(2n,0)$ starting with an up step, which may go u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For example, let π = {{1, 5}, {2, 3, 4, 7}, {6, 8}} ∈ S (8,3). There are 5 arcs in π, so we must add 4 vertices in order to get a partial matching in Q (12,5).…”
Section: Neighbor Alignments and Left Nestingsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, let π = {{1, 5}, {2, 3, 4, 7}, {6, 8}} ∈ S (8,3). There are 5 arcs in π, so we must add 4 vertices in order to get a partial matching in Q (12,5).…”
Section: Neighbor Alignments and Left Nestingsmentioning
confidence: 99%
“…There are 5 arcs in π, so we must add 4 vertices in order to get a partial matching in Q (12,5). We first add a singleton before the arc (2, 3) and a singleton before the arc (6,8). Then change the two 2-paths into left crossings from left to right.…”
Section: Neighbor Alignments and Left Nestingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these general results, various authors have studied classes of matchings avoiding a particular fixed pattern of small size. Jelínek, Li, Mansour and Yan [8] have shown that the matchings avoiding 1123 correspond bijectively to a certain class of lattice paths, and used this fact to obtain the formula…”
Section: Previous Workmentioning
confidence: 99%